Patients’ perspective on the therapeutic relationship and session quality: the central role of alliance - Stefana, Alberto; Fusar-Poli, Paolo; Vieta, Eduard; Youngstrom, Eric A. (Frontiers in Psychology, 2024)
In this study, we examined how four components of the therapeutic relationship-working alliance, real relationship, and positive and negative affective reactions of the patient towards their therapist-relate to each other and to the psychotherapy session outcome, from the patient's point of view. Our simple comprised 700 adult patients in individual psychotherapy who were recruited and participated online. They underwent a baseline evaluation of their most recent therapy session, which encompassed a series of validated self-report measures focused on specific elements of the therapeutic relationship. The results revealed that, from the patient's perspective, working alliance, real relationship, and positive affective reactions toward the therapist were positively correlated with session outcome, while negative affective reactions were negatively correlated. All components predicted session outcome when simultaneously included in a regression model.Collectively, these four components accounted for 30% of the variance in session outcome. Factor analysis revealed four distinct factors, underlying perceptions of the therapeutic relationship.Notably, the bond dimension of the alliance was sufficiently different from the task and goal dimensions, warranting consideration as a distinct construct. These findings, although crosssectional, lay the groundwork for a more nuanced investigation of multiple dimensions of the therapeutic relationship.